Extraction, optimization and characterization of Inca Inchi Oil and its oil meal for chewable oil tablets and cookies formulation - Christopher, Jeffi (2024)
Inca Inchi Oil (Plukenetia volubilis L.), rich in essential fatty acid faces challenges that limit its practical applications. These include susceptibility to oxidation, low extraction yields and quality from conventional methods. This study aims to enhance oil yield, antioxidant properties, and quality through heat pretreatment (microwave and hot air oven) and enzyme-assisted extraction, develop chewable oil tablets, and evaluate the acceptability of its press cake in cookies. The study showed that microwave pretreatment of inca inchi seeds for 4 min resulted in the highest oil yield (43.39%), compared to control (37.76%). Pre-treated oil samples had better quality in terms of free fatty acids (<1%) and peroxide values (<8 meqO2/kg). The 2,2-diphenyl- 1- 1picrylhydrazyl (DPPH) and 2,2´-azino-bis 3-ethylbenzothiazoline-6-sulfonic acid (ABTS) study, showed that pretreated oil had good radical scavenging activity (70% and 90%). The extraction efficiency of the enzymes Neutrase 0.8L and Viscozyme L were evaluated. The study showed that, among the enzymes, Neutrase 0.8L was more efficient in extracting the oil (46.77%) when compared to Viscozyme L (14.7%). The oil extracted had low free fatty acid (<1%) and peroxide value (<8 meqO2/kg). The oil showed high scavenging activity (73% and 82%) as analyzed by DPPH and ABTS assays. Spray drying was used to develop microcapsules of blends of inca inchi oilvirgin coconut oil and inca inchi oil-red palm oil. Evaluation of the microcapsules showed that the microcapsules exhibited good flowability and low moisture content (<3%). The microcapsules showed reduction in fatty acids and the retention of β carotene was about 60%. Through the process of optimization, high encapsulation efficiency (>90%) was achieved at 40% and 160°C for total solids and inlet air temperature, respectively for both the samples. Chewable oil tablets were developed from spray dried encapsulates by direct compression technique. Analyses of the tablets in terms of attributes such as hardness, disintegration time and friability showed that the tablets were within the standard value as recommended by United States Pharmacopoeia. The invitro release of oil showed that the % of oil release was higher in gastrointestinal condition (8.5-18.67%) than in gastric condition (6.2-7.78%). Storage studies on the attributes of the chewable tablets indicated significant differences (p<0.05) in the attributes, but they remained within the acceptable limits over two months at 4°C and 25°C. Additionally inca inchi oil press cake at various proportions (5%, 10%, 20% and 30%) were used to develop cookies. The study observed that cookies containing 10% oil meal had high protein content (13.03%) against control (4.89%). The hardness of the cookies formulated with press cake were low (2.52-3.22 N) compared to control (3.30 N). Moisture stability of the cookies stored for a month showed that water activity remained below 0.6. Sensory analysis favored cookies with 10% formulation, suggesting its potential for developing healthier cookies. Overall, the study shows that by using innovative extraction techniques, developing dietary supplements, and incorporating press cake into food products, the study paves the way for its application benefiting both consumers and the industry.